Dampak Efektivitas Sistem Informasi Akuntansi dan Penggunaan Teknologi Informasi Akuntansi terhadap Kinerja Individu di Sektor Publik - Bintusalihi; Budi Safatul (BE-HISZ : Journal of Economics and Accounting, 2025)
This study aims to examine the effect of accounting information system effectiveness and the use of accounting information technology on individual performance at the Banda Aceh Mayor’s Office. A quantitative approach was employed using a survey method through questionnaires distributed to 28 employees directly involved in accounting information systems and accounting technology utilization. The sampling technique used was census sampling, while data were analyzed using multiple linear regression with SPSS version 23. The results indicate that accounting information system effectiveness and the use of accounting information technology simultaneously have a significant effect on individual performance. Partially, accounting information system effectiveness has a positive and significant effect on individual performance, whereas the use of accounting information technology does not show a significant effect. These findings suggest that improving individual performance in the public sector is not merely driven by the intensity of technology usage, but is strongly influenced by the effectiveness of accounting information systems, including system quality, information quality, and user satisfaction. This study provides practical implications for local governments in designing and optimizing effective accounting information systems to enhance employee performance.